Systemic Administration of Avian Defensin 7: Distribution, Cellular Target, and Antibacterial Potential in Mice - Bailleul, Geoffrey; Guabiraba, Rodrigo; Virlogeux-Payant, Isabelle; Lantier, Isabelle; Trotereau, Jérôme; Gilbert, Florence B.; Wiedemann, Agnès; Trotereau, Angélina; Velge, Philippe; Schouler, Catherine; Lalmanach, Anne-Christine (Frontiers in Microbiology, 2019)
Defensins are natural antimicrobial peptides. The avian beta defensin AvBD7 isolated from the chicken bone marrow possess broad antibacterial spectrum and strong resistance to proteolysis. However, its ability to fight systemic infections of major concern for public health, such as salmonellosis, is unknown. As a first approach, fluorescence labelling of AvBD7 allowed to track its systemic distribution after intra-peritoneal injection in mice using whole body live imaging. It was associated to peritoneal cells and to deeper organs such as the liver. In the next step, the use of labelled AvBD7 allowed to observe its interaction with murine macrophages in culture. After incubation, it was able to penetrate inside the cells through an endocytosis-like mechanism. Furthermore, natural AvBD7 contributed to the control of intracellular multiplication of a multidrug resistant Salmonella strain, after incubation with infected macrophages. Finally, administration in a model of systemic lethal Salmonella infection in mice led to significant improvement of mouse survival, consistently with significant reduction of the liver bacterial load. In conclusion, the results reveal a hitherto unknown intracellular antibacterial effect of AvBD7 in Salmonella target cells, and support AvBD7 as a candidate of interest for the treatment of infectious diseases caused by multidrug resistant pathogenic Enterobacteriaceae.